Habitus, Ngêng, dan Estetika Bunyi Mlèsèt dan Nggandhul pada Karawitan - Prasetya, Hanggar Budi; Haryono, Timbul; L. Simatupang, Lono L. (UI Scholars Hub, 2011)
The paper explains about mlèsèt and nggandhul phenomena in the Javanese Karawitan in the perspective of Piere Bourdieu’s sociology of arts. The datas were collected through interviews with pengrawit,or gamelan players, and observation of gamelan played during the performance of Yogyakarta wayang. The research shows that mlèsèt and nggandhul aresound aesthetics for the listeners and habitus of the gamelan players. Therefore, a gamelan player should possess his ngêng in order to precisely play the correct rhythm of mlèsèt and nggandhul.